Beyond Urban Development: The Political Economy of The Decision to Build A New Administrative Capital [NAC] - Medhat, Arsany (AUC Knowledge Fountain, 2024)
Following major societal upheavals, regimes often embark on grandiose infrastructure projects, particularly new capital cities. This thesis delves into the political-economic motivations behind such seemingly monumental undertaking, taking the case of Egypt's New Administrative Capital (NAC) as its prime example. Through meticulous analysis, it argues that three key drivers—legitimization, legibility, and clientelism—underpin this decision, ultimately fostering a process of power consolidation. Legitimization: The NAC serves as a potent symbol of a "new era," offering the post-upheaval regime a platform to showcase its modernity, efficiency, and commitment to progress, thereby bolstering its legitimacy in the eyes of both domestic and international audiences. Legibility: The planned capital, with its meticulously controlled physical and social organization, promises to render the population and their activities more "legible" to the state, facilitating surveillance, resource allocation, and ultimately, political control. Clientelism: The construction and management of the NAC presents a vast network of lucrative contracts and patronage opportunities, fostering loyalty and cementing the regime's ties with select economic and political elites. These interrelated motives, intertwined with the pursuit of control and influence, constitute what this thesis terms power consolidation. By examining the NAC through this lens, it sheds light on the broader phenomenon of mega-projects as instruments for regimes to not only rebuild infrastructure but also to reshape the political landscape in their favor.